2001
DOI: 10.2105/ajph.91.7.1094
|View full text |Cite
|
Sign up to set email alerts
|

Mental health services for youths in foster care and disabled youths

Abstract: OBJECTIVES: This study assessed whether mental health services for youths differ with respect to medical assistance aid category. METHODS: Computerized claims for 15,507 youths with Medicaid insurance in a populous county of a mid-Atlantic state were used to establish population-based prevalence estimates of mental disorders and psychotherapeutic treatments during 1996. RESULTS: An analysis of service claims revealed that the prevalence of mental disorders among youths enrolled in foster care (57%) was twice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(48 citation statements)
references
References 42 publications
5
43
0
Order By: Relevance
“…Pastor and Reuben (2005) controlled for these variables as well as comorbid learning disability, yet found that neither of these factors accounted for the noted race differenced in ADHD diagnosis. Similar results were found by dosReis, Zito, Safer, and Soeken (2001) in a population-based study of ADHD in children with Medicaid insurance in a suburban mid-Atlantic community.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Pastor and Reuben (2005) controlled for these variables as well as comorbid learning disability, yet found that neither of these factors accounted for the noted race differenced in ADHD diagnosis. Similar results were found by dosReis, Zito, Safer, and Soeken (2001) in a population-based study of ADHD in children with Medicaid insurance in a suburban mid-Atlantic community.…”
Section: Resultssupporting
confidence: 85%
“…Table 2 shows a medium effect pooled across studies. Three of the five studies found more ADHD in Caucasian Americans than in African Americans (dosReis et al, 2001; Pastor & Reuben, 2005; Stevens et al, 2005). The other two studies showed that prevalence rates were equal across these two racial groups (Angold et al, 2002; Rowland et al, 2002); both of the latter two relied on data collected from North Carolina public schools.…”
Section: Resultsmentioning
confidence: 95%
“…Consistent with previous reports, the prevalence of antipsychotic use (6, 11) and clinically diagnosed mental disorders (8, 9) among foster youth was substantially higher than that among non-foster Medicaid youth. While demographic characteristics explained a small portion of the difference, mental disorder diagnoses explained a larger share, reducing the odds ratio from 4.19 (adjusted for demographics) to 2.59 (adjusted for demographics and diagnoses).…”
Section: Discussionsupporting
confidence: 90%
“…Also, dos Reis et al [35] found higher percentages of mental health assistance use among children on Medicaid because they were in foster care (62%), in comparison with groups receiving Medicaid because of physical, or psychological disability (29%) or poverty (4%). Fostered children had increased rates of attention-deficit hyperactivity disorder (ADHD), depression and adjustment disorders compared with the other groups.…”
Section: Long Term Effects Of Institutionalizationmentioning
confidence: 99%